Examining the Impact of Social Media Marketing, Product Quality, and Online Reviews on Purchase Decisions through Purchase Interest: Evidence from Somethinc Lip Glaze Consumers - Anggraini, Reni; Kencanawati, Mella Sri; Noviyana, Syntha; Dewi, Safira Rama (Review: Journal of Multidisciplinary in Social Sciences, 2025)
In development era digital has bring change significant in various aspect life, including business activities and public consumption. Advances in information technology, communication and the internet encourages business actors from small to large scale to take advantage of digitalization as a means of expanding market reach and increasing competitiveness. The phenomenon digitalization participate give influence on development industry beauty Which now become Wrong One sector with growth rapidly in Indonesia. Objective study This is analyze influence social media marketing , product quality, and online customer reviews on purchasing decisions through interest buy as well as For know variables where Which most dominant to interest buy And decision purchase product Lip Glaze Something. Method analysis on study This using quantitative primary data. The data obtained came from distributing questionnaires to 150 respondents were consumers who had purchased the Somethinc Lip Glaze product. The analysis tool used in this study is SmartPLS 4.0 by conducting a validity test. (convergent validity, discriminant validity, and Average Variance Extracted (AVE)), reliability test ( composite reliability and Cronbach's alpha ), R- square , Predictive Relevance (Q2), Model Fit, test Hypothesis ( Path Coefficient And Specific Indirect Effect ). Results study This seen from Path Coefficient and Specific Indirect Effect which shows that social media marketing and quality product influential to decision purchase. Whereas, on line customer review No influence on purchasing decisions. Then, in the results of the path coefficient test calculation show that social media marketing, quality product, And on line customer review influential to purchasing decisions through interest buy.